Fishery, biology and population dynamics of Metapenaeus dobsoni (Miers 1878) from Kerala, south-west coast of India - Chakraborty, Rekha Devi; Nandakumar, G.; Maheswaruduand, G.; Chellapan, K. (Indian Journal of Fisheries, 2014)
The fishery and population dynamics of the flowertail shrimp Metapenaeus dobsoni along the Kerala coast was studied based on landings at Cochin Fisheries Harbour during the period 2005 to 2007. Kerala ranked first in the production of M. dobsoni (>50%), followed by Tamil Nadu. The average annual catch and catch per unit effort of M. dobsoni was 2,526 t and 115.2 kg respectively. It formed 70% of the total penaeid shrimps landed in trawls. Peak landings were observed from April to June followed by November to January. The size range of male and female was 51-100 mm and 51-125 mm, respectively. The male-female sex ratio was 1:1.21. Mature females occurred throughout the period of observation and the size at first maturity was 60 mm. Growth parameters Lâˆž, K and t0 were estimated as 103 mm, 2.01 y-1, -0.00018 and 130, 2.51 y-1, -0.000046 for male and female, respectively. Length at recruitment (Lr) was found to be 53 mm for both sexes while the length at 50% capture (Lc50) was 65 mm for males and 70 mm for females. Recruitment was found to occur in most of the months with peak (>70%) during June to November. Natural mortality (M), fishing mortality (F), total mortality (Z), exploitation rate (E) and Emax were 2.17, 5.57, 7.74, 0.72, 0.81 and 2.00, 5.83, 7.83, 0.74, 0.680 for males and females, respectively. Higher values of E indicated that the resource is overexploited. Results of Beverton and Holt yield per recruit analysis and Thompson and Bell analysis revealed that at the present fishing effort, spawning stock biomass was above 20% suggesting that the fishery is sustainable.